Knowledge and awareness of risk factors for cardiovascular disease in the Ga-Rankuwa community - Li Yuqiu; Susanna Catherina Dreyer Wright (AOSIS, 2008)
Cardiovascular disease causes 30% of deaths globally. By comparison, infectious disease accounts for 10% of global mortality. As these statistics indicate, cardiovascular disease is the most common cause of death in the world. In South Africa, through urbanisation and changes in lifestyle and dietary habits, the prevalence of risk factors and, by extension, the resulting morbidity and mortality from cardiovascular disease in black people, are expected to increase. Owing to the natural progression of the disease, the first 'westernised illness' is hypertension, which is very prevalent among the black population. Knowledge and awareness of risk factors are essential components of behaviour change; however, little is known about the knowledge and awareness of cardiovascular disease among the working-age people in the Ga-Rankuwa community. The purpose of the study was therefore to determine the knowledge and awareness of the identified risk factors among the working-age people (18-40 years old) in the Ga-Rankuwa community. The design was a quantitative survey. The study sample (n=604) was selected from zones 1, 2, 4 and 16 of Ga-Rankuwa to determine the prevalence of risk factors for cardiovascular disease. Only people with an identified risk factor were included in the knowledge and awareness survey (n=551). Data was gathered from July to October 2005. The data gathering was self- reported with a structured questionnaire. Data were analysed using descriptive statistics and statistical analysis. The results obtained from the knowledge and awareness survey indicate that knowledge and awareness of the risk factors for cardiovascular disease are low in the Ga-Rankuwa community. Opsomming Kardiovaskulêre siektes veroorsaak 30% van sterftes wêreldwyd. In vergelyking veroorsaak aansteeklike siektes net 10% van die sterftes wêreldwyd. Kardiovaskulêre siektes is dus die mees algemene oorsaak van sterftes. In Suid-Afrika, as gevolg van verstedeliking en gepaardgaande veranderende dieetgewoontes en lewenstyl, is die verwagting dat die voorkoms van risikofaktore in swartmense sal verhoog en daarmee saam ook die gevolglike morbiditeit en mortaliteit aan kardiovaskulêre siektes. Hipertensie is die eerste 'westerse siekte' vanweë die natuurlike verloop van kardiovaskulêre siektes en is meer algemeen in die swart gemeenskap. Kennis en bewustheid van die risikofaktore is 'n noodsaaklike komponent om die nodige gedragsverandering te bewerkstellig, maar min inligting is oor die vlak van kennis en bewustheid van kardiovaskulêre siektes in die Ga-Rankuwa-gemeenskap beskikbaar. Die doel van die studie was dus om die kennis en bewustheid van risikofaktore vir kardiovas-kulêre siektes in 'n werksouderdom groep persone (18-40 jaar oud) in Ga-Rankuwa te bepaal. 'n Kwantitatiewe opname is uitgevoer. 'n Sensussteekproef is vanuit sone 1, 2, 4, and 16 in Ga-Rankuwa getrek om die voorkoms van risikofaktore vir kardiovaskulêre siektes te bepaal (n=604). 'n Subgroep persone, slegs dié wat met 'n risikofaktor vir kardiovaskulêre siektes diagnoseer is, is in die opname ingesluit (n=551). Die data is vanaf Julie tot Oktober 2005 deur middel van selfrapportering en 'n gestruktureerde vraelys ingesamel en is deur beskrywende statistiek ontleed. Die resultate dui daarop dat daar oor die algemeen 'n lae vlak van kennis en bewustheid van die risikofaktore vir kardiovaskulêre siektes in die Ga-Rankuwa-gemeenskap is.